2017
DOI: 10.1097/txd.0000000000000651
|View full text |Cite
|
Sign up to set email alerts
|

A Case Report of Paradoxical Air Embolism Caused by Intrapulmonary Shunting During Liver Transplantation

Abstract: Supplemental digital content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Transesophageal echocardiography is considered to be the most sensitive monitor for air embolism. TEE may be useful in identifying the size and location of the air embolism as well as intracardiac shunts that allow passage of the air into the arterial circulation [ 5 ]. This modality was not used during this case.…”
Section: Discussionmentioning
confidence: 99%
“…Transesophageal echocardiography is considered to be the most sensitive monitor for air embolism. TEE may be useful in identifying the size and location of the air embolism as well as intracardiac shunts that allow passage of the air into the arterial circulation [ 5 ]. This modality was not used during this case.…”
Section: Discussionmentioning
confidence: 99%
“…PAE is extremely rare when no intracardiac shunt has been identified, but has been reported following non-neurosurgical cases [6-8]. In 2012, Schlundt et al reported a case of left ventricular air crossover in the absence of a PFO in a neurosurgical patient undergoing resection of a cerebellopontine angle lesion in the sitting position [9].…”
Section: Discussionmentioning
confidence: 99%
“…Subclinical PAE during orthotopic LT is frequently detected using intraoperative transesophageal echocardiography (TEE). PAE can involve the coronary arteries (leading to myocardial ischemia) or cerebral vessels (leading to ischemic stroke), but serious complications or cases of hemodynamic collapse due to PAE are rare [ 2 4 ]. Here, we present a case of severe biventricular dysfunction following allograft reperfusion during an orthotopic LT with hemodynamic collapse preceded by detection of transpulmonary air into the left atrium, left ventricle, and ascending aorta using TEE and ST-segment changes on electrocardiography (ECG) monitoring.…”
Section: Introductionmentioning
confidence: 99%